Formulation and in vitro characterization of inhalable dasatinib-nanoemulsion as a treatment potential against A549 and Calu-3 lung cancer cells - Tulbah, Alaa S. (International Journal of Health Sciences, 2025)
Objective: Dasatinib (DTB) is a second-generation tyrosine kinase inhibitor that was found it could help with lung cancer. However, DTB has low aqueous solubility and poor bioavailability due to its incomplete absorption and high ﬁrst-pass effect. The objective of this study was to improve DTB’s solubility, delivery, and efficacy as a potential lung cancer treatment by developing an inhalable DTB-nanoemulsion (DNE) formulation. Methods: The DNE formulation was prepared by the spontaneous emulsification method, using oleic acid as the oil phase and a mixture of Kolliphor RH 40 and dipropylene glycol as surfactant. Compared with free DTB, the DNE formulation enhanced the aqueous solubility, flow property, and delivery of DTB to the lungs with a good fine-particle dose, fine-particle fraction, and mass median aerodynamic diameter. Results: The DNE formulation was safe on lung cancer cells when the cell viability and toxicity were evaluated and IC50 values were found to be 0.0431 μg/mL and 0.0443 μg/mL on A549 and Calu-3 cells, respectively. Moreover, DNE formulation significantly increased its anti-cancer effectiveness against A549 and Calu-3 lung cancer cells by interfering with cell cycle progression through apoptosis or cell cycle arrest. Conclusion: The nanoemulsion formulation has the potential to be an effective carrier for DTB, which could possibly be used to treat lung cancer.